Willingness to pay for urban waste disposal (Provincial Municipality of Tambopata, Madre de Dios, Peru) - Colquehuanca Vilca, Julián (2020)
The management of urban waste in the Provincial Municipality of Tambopata induces the environmental deterioration of the soil, water,and biodiversity along with the proliferation of diseases. The objective was to determine the citizens’ preference in reducing, recycling,reusing, recovering (4R) and their willingness to pay (DAP) for the elimination of urban waste from the classification level. Theinformation was collected through 406 surveys of heads of households by multiple-stage random sampling, complemented by in-depthinterviews; the method of choice experiments (EE) was used to determine the preference of the public user, using thelogitandmixlogitmodel to estimate the probability of the DAP. The results indicate that 68.72% of users do not recycle any waste, but are predisposedto do so. Of these, 28.72% have a preference for RR (waste collection) with the practice of “4R” for segregation purposes; 28.26% forDR (waste disposal) in sanitary landfill instead of open dumps; 26.08% bet on CR (zero waste) with implication of waste reduction; and16.94% choose Status quo of emotional state of the moment as undecided. In sum, 83.06% of citizens have the DAP in exchange foracceptable human health and socio-environmental well-being. It is concluded that the users of Puerto Maldonado have the willingness topay 122 soles per year, in exchange for the elimination of urban waste, being a leading part of sustainability.